Transdisciplinary engineering design process - Ertas, Atila, 1944- (Hoboken, NJ : John Wiley & Sons, Inc, 2018)
In recent years, the number of complex problems to be solved by engineers has multiplied exponentially. Transdisciplinary Engineering Design Process outlines a collaborative approach to the engineering design process that includes input from planners, economists, politicians, physicists, biologists, domain experts, and others that represent a wide variety of disciplines. As the author explains, by including other disciplines to have a voice, the process goes beyond traditional interdisciplinary design to a more productive and creative transdisciplinary process.
Written for members of the academy as well as industry leaders, Transdisciplinary Engineering Design Process is an essential resource that offers a new perspective on the design process that invites in a wide variety of collaborative partners.
Systemic thinking and complex problem solving -- Transdisciplinary design process -- Project management and product development -- Transdisciplinary sustainable development -- Design for manufacture -- Design analyses for material selection -- Statistical decisions -- Risk, reliability and safety -- Optimization in design -- Modeling and simulation -- Engineering economics -- Engineering ethics -- Communications in engineering.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on August 14, 2018).
Keywords: Engineering design; Multidisciplinary design optimization; Electronic books